DISPUTE SETTLEMENT NORM OF ESTATE DISTRIBUTION ON ADAT PEOPLE OF MINANGKABAU (WEST SUMATRA) - Poespasari, Ellyne Dwi (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Principally, dispute settlement of estate distribution on Minangkabau People is done by deliberation. If its settlement through deliberation is failed, an effort to solve the dispute through court needs to be conducted. This paper studies first, how is the opinion of judicial institution in the dispute of estate distribution on Minangkabau people; second, how is the implication of estate distribution on Minangkabau people after judge’s verdict. This is normative research with statute approach and case approach. The result of this research shows that there is the possibility of judicial institution’s verdict in the dispute settlement of estate distribution which is contradicted with adat law of Minangkabau (Matrilineal kinship). However, if it is seen from the legal perspective, estate distribution of Minangkabau people after judge’s verdict can be a breakthrough that is able to change the value of old adat law into the new one. Keywords: Dispute settlement, estate distribution, matrilineal kinship.